2019
DOI: 10.2166/wqrj.2019.050
|View full text |Cite
|
Sign up to set email alerts
|

High performance adsorption of hazardous triphenylmethane dye-crystal violet onto calcinated waste mussel shells

Abstract: Synthetic dyes are harmful to human beings, and the removal of colour from process or waste effluents is environmentally important. Crystal violet (CV) is a typical triphenylmethane dye, which is widely used in textile dyeing and paper printing industries. The present study shows that granulated and calcinated waste mussell shells (CWMS) can be used as a potential low-cost and locally available adsorbent for the removal of CV from aqueous solutions. The adsorption capacities of the CWMS for CV were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Hence, the feasibility of the process depend mainly on the increase in entropy during adsorption. Similar trends in thermodynamics have also been observed for the adsorption of CV onto calcinated waste mussel shells [42], MG onto waste pea shells [43] and Cr(VI) onto activated carbon [44].…”
Section: Thermodynamic Investigationssupporting
confidence: 77%
“…Hence, the feasibility of the process depend mainly on the increase in entropy during adsorption. Similar trends in thermodynamics have also been observed for the adsorption of CV onto calcinated waste mussel shells [42], MG onto waste pea shells [43] and Cr(VI) onto activated carbon [44].…”
Section: Thermodynamic Investigationssupporting
confidence: 77%
“…They anticipated that by combining these proteins with their specific structure, would facilitate the elimination of the dye and heavy metals. Dandil et al [ 23 ] also examined that calcined waste mussels shells act as adsorbents to remove the dye. This result has confirmed that the presence of FMs in water bodies has significant importance for removing dyes from waste or polluted water.…”
Section: Discussionmentioning
confidence: 99%
“…9. This can be attributed to the aggregation or overlapping of adsorption sites, which reduces the overall adsorption surface area available for the dye and increases the diffusion path length [40][41][42].…”
Section: Effect Of Adsorbent Dosementioning
confidence: 99%